2021
DOI: 10.1097/md.0000000000025849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupoint massage combined with relaxation therapy on patients with postoperative fatigue syndrome after lumbar surgery

Abstract: Background : Lumbar disc herniation (LDH) is a common disease in orthopedics. Surgery is shown to provide significant faster relief of pain compared to conservative therapy. However, due to the influence of surgical trauma, anesthesia and other perioperative stress factors, patients may have complications. Among them, postoperative fatigue syndrome (POFS) is a common complication. Traditional Chinese medicine or integrated traditional Chinese and Western medicine have been proved to be effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…[21–33] Seven studies reported the blinding of outcome assessment, [21,23,26,27,29,30,33] and the rest were unclear. For other sources of bias, 2 were high-risk, [25,26] 7 were unclear, [21,22,24,28,31–33] and the rest were low-risk.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[21–33] Seven studies reported the blinding of outcome assessment, [21,23,26,27,29,30,33] and the rest were unclear. For other sources of bias, 2 were high-risk, [25,26] 7 were unclear, [21,22,24,28,31–33] and the rest were low-risk.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Three of these trials reported the stages of cancer. [23,26,31] Five trials had participants in the perioperative period, [21,24,26,27,31] 3 had a treatment status of undergoing chemotherapy, [22,29,32] while the others had multiple treatment statuses or unreported treatment statuses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations